Acquisition Size and Frequency Effects on Outperforming the Market : Evidence from Finland during Interest Rate hikes - Suomalainen, Anton (My University, 2024)
The purpose of thesis is to find out what kind of acquisition strategy works during rising interest rate environment in Finland. The acquisition strategies are defined based on the size and frequency of acquisitions made during specific period. The period for the study is from beginning of 2022 until end of 2023 when European Central Bank raised interest rates on a historical pace. There is a prior literature, which notes that serial acquirer companies, which make various small acquisitions, outperform in the market and companies making large acquisitions underperform the market. The topic has not been fully studied in Finnish Stock Market nor during rising interest rate environment. The study consists of literature review on the topic, which consists of factors altering the success of acquisitions and reasons for failing acquisition. The literature review includes prior findings on what kind of acquisition strategies by size and frequency have performed the best. The empirical part of the study consists of regression analysis and subsample testing between acquisition strategies based on data from listed companies in Finland. The findings estimate that companies who didn’t perform in mergers and acquisitions during rising interest rates performed better than companies who did. The study didn’t find statistically significant performance differences between acquisition strategies in the Finnish Stock Market during this period.

Tutkielman tarkoitus on selvittää, millainen yritysostostrategia toimii nousevien korkojen aikaan Suomessa. Yritysostostrategiat määritellään yritysostojen koon ja määrän mukaan tietyllä ajanjaksolla. Tutkimusajankohta on vuoden 2022 alusta vuoden 2023 loppuun, milloin Euroopan keskuspankki nosti ohjauskorkoja historiallisen nopeasti. Aiempi kirjallisuus osoittaa, että sarjayhdistelijäyritykset, jotka tekevät useita pieniä yritysostoja menestyvät markkinoilla paremmin, kun taas suuria yritysostoja tekevät yritykset alisuoriutuvat markkinoilla. Tätä aihetta ei ole kattavasti tutkittu Suomen osakemarkkinoilla eikä nousevien korkojen aikaan. Tutkimus koostuu kirjallisuuskatsauksesta, jossa tarkastellaan tekijöitä, jotka vaikuttavat yritysostojen onnistumiseen sekä syitä epäonnistuneisiin yritysostoihin. Kirjallisuuskatsauksessa käsitellään aiempia tutkimustuloksia siitä, millaiset yritysostostrategiat kohdeyritysten koon ja määrän suhteen ovat menestyneet parhaiten. Tutkimuksen empiirinen osuus koostuu regressioanalyysistä ja otosryhmätestauksesta, joissa vertaillaan eri yritysostostrategioita Suomen pörssiyhtiöistä kerätyn datan perusteella. Tulokset osoittavat, että yritykset, jotka eivät tehneet fuusioita tai yritysostoja nousevien korkojen aikana, suoriutuivat paremmin kuin ne, jotka tekivät. Tutkimus ei löytänyt tilastollisesti merkitseviä eroja eri yritysostostrategioiden tuotoissa Suomen osakemarkkinoilla nousevien korkojen ajanjaksolta.
Keywords: acquisitions, mergers and acquisitions, serial acquirers, acquisition strategy, rising interest rates, stock market outperformance